Analisis Sistem Operasional Manajemen Persediaan dalam Menjaga Kualitas Bahan Baku pada Industri Coffee Shop ( Studi Kasus di Kedai Aman Kuba Coffee Yogyakarta ) - Dinda Mustika F. Alfatan; Imron Yaskur; Kristiana Sri Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study explores how Aman Kuba Coffee Shop in Yogyakarta manages its raw material inventory to maintain product quality and deliver excellent customer service. Effective inventory management is crucial to ensuring consistent coffee flavor and customer satisfaction. This research employs a qualitative method using a case study approach, involving direct observation of inventory management practices at the shop. Data were collected through interviews with the owner, manager, baristas, and customers; on-site observations; and examination of documents such as stock records and quality standards. The findings reveal that a structured and consistent inventory system plays a key role in preserving raw material quality. Moreover, efficient inventory management positively influences customer satisfaction and supports the overall operational efficiency of the coffee shop.